ANALISA POTENSI BERSAING PASAR TRADISIONAL TERHADAP PASAR MODERN DI KOTA AMBON - Fitria Karnudu (TAHKIM, 2017)
This article aims to find out compete potential of the traditional market against the modern market, and the impact of the development of a modern market to traditional markets. The traditional market potential, is the offered product are more still fresh products, the price is negotiable, cheap and affordable. But majority respondents stated that the location and condition of currently traditional market space is inadequate with facilities and amenities that do not support. Although many shortcomings, especially in terms of amenities, location and the convenience level for visitors, but the competitive potential of traditional markets still exist. This is due to in the traditional markets there are social factors and emotional closeness between the buyer and seller which are not found in the modern market. The Development of the modern market not affect indirectly to the traditional markets, but the presence of the modern market give consumers more options in choosing the type of goods will be consumed, and provide different options of shopping atmosphere. Key words: Potential, traditional market, modern market